Water-based epoxy zinc-rich coating for container and preparation method of water-based epoxy zinc-rich coating
By introducing epoxy resin modifier on the surface of zinc powder and adding modified graphene to the coating, the shortcomings in storage stability and mechanical properties of existing epoxy zinc-rich coatings have been solved, and higher corrosion and salt resistance have been achieved Fog performance, suitable for containers and other applications.
Patent Information
- Application Number
- CN202411672213.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
After adding excessive zinc powder to existing epoxy zinc-rich coatings, they tend to settle, have poor storage stability, reduce the mechanical strength of the paint film, and the compatibility of zinc powder with epoxy resin is poor, affecting the comprehensive performance of the coating.
By introducing an epoxy resin modifier with carboxyl and sodium sulfonate groups to the surface of the zinc powder, a highly dispersible zinc powder is formed, and modified graphene is added to the coating to improve the dispersion and compatibility of the coating.
It improves the storage stability of the paint and the mechanical properties of the paint film, enhances the corrosion resistance and salt spray resistance, and makes the paint suitable for containers and other application scenarios.
Smart Images

Figure BDA0005146150350000021 
Figure BDA0005146150350000022 
Figure BDA0005146150350000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy zinc-rich coatings, and in particular to a water-based epoxy zinc-rich coating for containers and a preparation method thereof. Background Art
[0002] Epoxy zinc-rich paint mainly consists of epoxy resin, zinc powder, anti-settling agent, curing agent, etc. It can play an excellent anti-corrosion performance through shielding, electrochemical protection, passivation and other effects. Usually the zinc powder content in epoxy zinc-rich paint is between 80-85%, but adding excessive zinc powder will cause easy sedimentation, poor storage stability, and reduced mechanical strength of the paint film. Adding graphene to epoxy zinc-rich paint can further improve the anti-corrosion performance of the paint.
[0003] Modifying the surface of zinc powder can improve its dispersibility, improve the interfacial bonding performance between zinc powder and epoxy resin, and help improve the storage stability and mechanical properties of the coating. Patent CN105385305B discloses a water-based epoxy zinc-rich coating rich in microcapsule structure modified zinc powder and its preparation, which forms a modified zinc powder with a strict microcapsule structure having a water-repellent effect by adsorbing and coating zinc powder with hydrolyzable multifunctional polymeric silane, improving the dispersibility of zinc powder in epoxy emulsion, and the obtained water-based epoxy zinc-rich coating has good storage stability, low VOC content, good adhesion to the substrate and other comprehensive properties. However, the patent cannot improve the compatibility between zinc powder and epoxy resin, which is not conducive to improving the mechanical properties of the paint film. Summary of the invention
[0004] The technical problem solved by the invention is to provide a water-based epoxy zinc-rich coating for containers with good mechanical properties and excellent anti-corrosion properties.
[0005] The technical scheme of the present invention is: a water-based epoxy zinc-rich coating for containers, which consists of component A and component B, wherein component A comprises 12-18 parts by weight of epoxy resin emulsion, 0.1-0.14 parts by weight of anti-flash rust agent, and 0.1-0.15 parts by weight of defoamer; component B comprises 70-80 parts by weight of modified highly dispersible zinc powder, 0.1-1 parts by weight of modified graphene, 2.6-3.2 parts by weight of polyamide curing agent, 10-15 parts by weight of propylene glycol methyl ether, 0.5-0.8 parts by weight of wetting agent, and 1.6-2.5 parts by weight of anti-settling agent.
[0006] The preparation method of highly dispersible zinc powder comprises:
[0007] (1) Add glutamic acid and sodium carbonate to water, stir and then add sodium 2-bromoethane sulfonate, wherein the molar ratio of glutamic acid, sodium hydroxide and sodium 2-bromoethane sulfonate is 1:(1-1.1):(1-1.1); heat to 75-80°C for reaction for 2-3h, cool and then add saturated sodium chloride solution, extract with ethyl acetate, concentrate the organic phase under reduced pressure, add the product to water, heat and evaporate to concentrate, cool in an ice water bath to crystallize, and dry to obtain sodium ethanesulfonate iminoglutaric acid. The reaction formula is:
[0008]
[0009] (2) Add epoxy resin and sodium ethanesulfonate iminoglutaric acid in a mass ratio of 100:(76-82) to ethylene glycol butyl ether and n-butanol, react at 80-90°C for 3-5h, add acetone after cooling, filter, wash with acetone, and dry to obtain an epoxy resin modifier. The reaction formula is:
[0010]
[0011] (3) Add zinc powder and epoxy resin modifier in a mass ratio of 100:(1-3) to water, ball mill in a high-speed ball mill for 1-2 hours, filter, and dry to obtain highly dispersible zinc powder.
[0012] Preferably, the preparation method of modified graphene includes: adding graphene oxide to thionyl chloride for reaction to obtain chlorinated graphene; then adding chlorinated graphene to dichloromethane, adding triethylamine and sodium ethanesulfonate iminoglutaric acid after ultrasonic dispersion, reacting for 18-24 hours, filtering, washing with water, and drying to obtain modified graphene.
[0013] Preferably, the mass ratio of graphene chloride, triethylamine and sodium ethanesulfonate iminoglutaric acid is 100:(120-500):(300-1200).
[0014] Preferably, the preparation method of the water-based epoxy zinc-rich coating for containers comprises: adding an anti-flash rust agent and a defoaming agent to an epoxy resin emulsion, stirring and dispersing, and obtaining component A.
[0015] Add modified highly dispersible zinc powder, modified graphene, polyamide curing agent, weight parts, wetting agent and anti-settling agent to propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain water-based epoxy zinc-rich coating for containers.
[0016] The technical effect of the invention is that the imino group of sodium ethanesulfonate iminoglutaric acid is reacted with the epoxy group of the epoxy resin, thereby introducing a carboxyl group and a sodium sulfonate group into the epoxy resin molecular chain, and the obtained epoxy resin modifier can interact with the surface of the zinc powder particles, thereby coating the epoxy resin molecular chain on the zinc powder surface, which is beneficial to reducing the agglomeration of the zinc powder particles and improving the dispersibility; after the epoxy resin molecular chain is coated on the surface, the compatibility of the zinc powder and the epoxy resin emulsion is better, thereby improving the storage stability of the epoxy zinc-rich coating and the mechanical properties and anti-corrosion and salt spray resistance of the paint film.
[0017] The graphene of the present invention is grafted and modified with sodium ethanesulfonate iminoglutaric acid, and carboxyl groups, sodium sulfonate and other groups are introduced on the surface. The graphene has good dispersibility and compatibility in epoxy resin emulsion, which is beneficial to improve the mechanical properties of the paint film, so that the paint film has higher impact resistance, corrosion resistance and salt spray resistance. It has good practical applications in containers, shipbuilding, bridges and the like. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] Graphene oxide of the present invention, model HL-GO, Shanghai Hanlang New Material Technology Co., Ltd. Epoxy resin emulsion, Guangzhou Si Tuyuan Chemical Co., Ltd. Defoamer, DF 5800C, Nanjing Chuhai New Material Technology Co., Ltd. Anti-flash rust agent, Defros-T750, Shenzhen Longdi Chemical Co., Ltd. Wetting agent, BYK9565, Shenzhen Longdi Chemical Co., Ltd. Anti-settling agent, BYK410, Shenzhen Longdi Chemical Co., Ltd.
[0020] Example 1
[0021] (1) Add 5 mmol glutamic acid and 5 mmol sodium carbonate to 8 mL water, stir and add 5 mmol sodium 2-bromoethane sulfonate, heat to 80°C for 3 h, cool and add saturated sodium chloride solution, extract with ethyl acetate, concentrate the organic phase under reduced pressure, add the product to water, heat and evaporate, cool in an ice-water bath for crystallization, and dry to obtain sodium ethanesulfonate iminoglutaric acid.
[0022] (2) Add 6 mL of n-butanol, 2 g of epoxy resin E44, and 1.52 g of sodium ethanesulfonate iminoglutaric acid to 10 mL of ethylene glycol butyl ether, react at 80° C. for 4 h, add acetone after cooling, filter, wash with acetone, and dry to obtain an epoxy resin modifier.
[0023] (3) Add 100 g of zinc powder (average particle size 1200 mesh) and 1 g of epoxy resin modifier to 100 mL of water, and ball mill in a high-speed ball mill for 1 h. Filter and dry to obtain highly dispersible zinc powder.
[0024] (4) Add 0.5 g of graphene oxide to 40 mL of thionyl chloride, react at 70 ° C in a nitrogen atmosphere for 18 hours, filter, wash with dichloromethane, and dry to obtain graphene chloride; then add 0.5 g of graphene chloride to 150 mL of dichloromethane, add 1.5 g of triethylamine and 3.8 g of sodium ethanesulfonate iminoglutaric acid after ultrasonic dispersion, react for 24 hours, filter, wash with water, and dry to obtain modified graphene.
[0025] (5) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of modified graphene, 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain water-based epoxy zinc-rich coating for containers.
[0026] Example 2
[0027] (1) Add 5 mmol glutamic acid and 5.5 mmol sodium carbonate to 10 mL water, stir and add 5.5 mmol sodium 2-bromoethane sulfonate, heat to 75°C for 2 h, cool and add saturated sodium chloride solution, extract with ethyl acetate, concentrate the organic phase under reduced pressure, add the product to water, heat and evaporate, cool in an ice-water bath for crystallization, and dry to obtain sodium ethanesulfonate iminoglutaric acid.
[0028] (2) Add 8 mL of n-butanol, 2 g of epoxy resin E44, and 1.64 g of sodium ethanesulfonate iminoglutaric acid to 10 mL of ethylene glycol butyl ether, react at 90° C. for 3 h, add acetone after cooling, filter, wash with acetone, and dry to obtain an epoxy resin modifier.
[0029] (3) Add 100 g zinc powder (average particle size 1200 mesh) and 3 g epoxy resin modifier to 150 mL water, and ball mill in a high-speed ball mill for 2 h. Filter and dry to obtain highly dispersible zinc powder.
[0030] (4) Add 0.5 g of graphene oxide to 50 mL of thionyl chloride, react at 60 ° C in a nitrogen atmosphere for 24 hours, filter, wash with dichloromethane, and dry to obtain graphene chloride; then add 0.5 g of graphene chloride to 200 mL of dichloromethane, add 2.5 g of triethylamine and 6 g of sodium ethanesulfonate iminoglutaric acid after ultrasonic dispersion, react for 24 hours, filter, wash with water, and dry to obtain modified graphene.
[0031] (5) Add 1.4 g of anti-flash rust agent and 1 g of defoamer to 120 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 750 g of modified highly dispersible zinc powder, 5 g of modified graphene, 26 g of polyamide 650 curing agent, 5 g of wetting agent, and 25 g of anti-settling agent to 150 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a container waterborne epoxy zinc-rich coating.
[0032] Example 3
[0033] (1) Add 6 mL of n-butanol, 2 g of epoxy resin E44, and 1.57 g of sodium ethanesulfonate iminoglutaric acid (prepared in the same manner as in Example 1) to 10 mL of ethylene glycol butyl ether, react at 80° C. for 5 h, add acetone after cooling, filter, wash with acetone, and dry to obtain an epoxy resin modifier.
[0034] (2) Add 100 g zinc powder (average particle size 1200 mesh) and 2 g epoxy resin modifier to 150 mL water, and ball mill in a high-speed ball mill for 2 h. Filter and dry to obtain highly dispersible zinc powder.
[0035] (3) Add 0.5 g of graphene oxide to 40 mL of thionyl chloride, react at 60 ° C in a nitrogen atmosphere for 24 hours, filter, wash with dichloromethane, and dry to obtain graphene chloride; then add 0.5 g of graphene chloride to 150 mL of dichloromethane, add 0.6 g of triethylamine and 1.5 g of sodium ethanesulfonate iminoglutaric acid after ultrasonic dispersion, react for 18 hours, filter, wash with water, and dry to obtain modified graphene.
[0036] (4) Add 1 g of anti-flash rust agent and 1.5 g of defoamer to 180 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 800 g of modified highly dispersible zinc powder, 10 g of modified graphene, 32 g of polyamide 650 curing agent, 6 g of wetting agent, and 25 g of anti-settling agent to 150 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a water-based epoxy zinc-rich coating for containers.
[0037] Comparative Example 1
[0038] (1) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of graphene oxide, 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a container waterborne epoxy zinc-rich coating.
[0039] Comparative Example 2
[0040] (1) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified zinc powder (average particle size 1200 mesh), 1 g of modified graphene (same preparation method as in Example 1), 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain water-based epoxy zinc-rich coating for containers.
[0041] Comparative Example 3
[0042] (1) Add 100 g zinc powder (average particle size 1200 mesh) and 1 g epoxy resin E44 to 100 mL water, and mill in a high-speed ball mill for 1 h. Filter and dry to obtain highly dispersible zinc powder.
[0043] (2) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of modified graphene (prepared in the same manner as in Example 1), 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a water-based epoxy zinc-rich coating for containers.
[0044] Comparative Example 4
[0045] (1) Add 100 g of zinc powder (average particle size 1200 mesh) and 1 g of sodium ethanesulfonate iminoglutaric acid (prepared in the same manner as in Example 1) to 100 mL of water, and mill in a high-speed ball mill for 1 h. Filter and dry to obtain highly dispersible zinc powder.
[0046] (2) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of modified graphene (prepared in the same manner as in Example 1), 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a water-based epoxy zinc-rich coating for containers.
[0047] Comparative Example 5
[0048] (1) Add 100 g zinc powder (average particle size 1200 mesh) and 1 g stearic acid to 100 mL water, and mill in a high-speed ball mill for 1 h. Filter and dry to obtain highly dispersible zinc powder.
[0049] (2) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of modified graphene (prepared in the same manner as in Example 1), 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a water-based epoxy zinc-rich coating for containers.
[0050] Comparative Example 6
[0051] (1) Add 100 g of zinc powder (average particle size 1200 mesh) and 1 g of sodium dodecylbenzene sulfonate to 100 mL of water, and mill in a high-speed ball mill for 1 h. Filter and dry to obtain highly dispersible zinc powder.
[0052] (2) Add 1.3 g of anti-flash rust agent and 1.5 g of defoamer to 160 g of epoxy resin emulsion, stir and disperse to obtain component A. Add 700 g of modified highly dispersible zinc powder, 1 g of modified graphene (prepared in the same manner as in Example 1), 30 g of polyamide 650 curing agent, 8 g of wetting agent, and 16 g of anti-settling agent to 100 g of propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain a water-based epoxy zinc-rich coating for containers.
[0053] The storage stability of the coating was tested according to the method of GB / T 6753.3-1986. The storage temperature was 25°C and the storage time was 7-21 days. No polyamide 650 curing agent was added to the coating during the test.
[0054] The coating was sprayed on the surface of the substrate and cured at 120°C for 4 hours to form a paint film coating.
[0055] Impact resistance was tested according to GB / T 1732-2020. Salt spray resistance was tested according to GB / T 1771-2007. Cross-cut test and adhesion grade test were performed according to GB / T 9286-2021.
[0056] Table 1: Storage stability test
[0057]
[0058]
[0059] Table 2: Adhesion, impact resistance, and salt spray resistance tests
[0060] Adhesion grade Impact resistance (cm) Salt spray resistance (h) Example 1 0 50 528 Example 2 0 60 672 Example 3 1 55 624 Comparative Example 1 0 40 480 Comparative Example 2 6 30 336 Comparative Example 3 6 30 336 Comparative Example 4 2 45 432 Comparative Example 5 3 45 384 Comparative Example 6 2 45 408
[0061] As shown in Table 1 and Table 2, the epoxy zinc-rich coating of Embodiment 1-3 has no sedimentation at the bottom after being stored for 7-21 days, and has good storage stability. This is because the epoxy resin modifier contains more carboxyl and sodium sulfonate groups, which can interact with the surface of zinc powder particles, so that the epoxy resin molecular chain is coated on the surface of zinc powder, which is conducive to reducing the agglomeration of zinc powder particles and improving dispersibility, and after the epoxy resin molecular chain is coated on the surface, the compatibility of zinc powder and epoxy resin emulsion is better, thereby improving the storage stability of epoxy zinc-rich coating and the mechanical properties and anticorrosion and salt spray resistance of the paint film. And graphene is grafted and modified by sodium ethanesulfonic acid iminoglutaric acid, and carboxyl, sodium sulfonate and other groups are introduced on the surface. The dispersibility and compatibility in epoxy resin emulsion are also very good, which is conducive to improving the mechanical properties of the coating film, so that the paint film has higher impact resistance, anticorrosion and salt spray resistance and other properties.
[0062] Compared with Example 1, the graphene oxide in Comparative Example 1 has not been grafted with sodium ethanesulfonate iminoglutaric acid, the graphene oxide is easy to agglomerate, and its compatibility and dispersibility with the epoxy resin emulsion are poor, resulting in the paint film having slightly lower impact resistance, corrosion resistance and salt spray resistance than Example 1, and after long-term storage, there is a trace amount of graphene oxide precipitation at the bottom of the coating.
[0063] The zinc powder of Comparative Example 2 has not been surface modified, is easily agglomerated, has poor dispersibility, has poor storage stability of the coating, and has poor impact resistance, corrosion resistance, and salt spray resistance of the coating film.
[0064] Comparative Example 3 Epoxy Resin E44 does not contain carboxyl groups or sodium sulfonate groups, and cannot modify the surface of zinc powder particles. The zinc powder is easily agglomerated and has poor dispersibility. The storage stability of the coating is poor, and the impact resistance, corrosion resistance, and salt spray resistance of the coating film are poor.
[0065] Compared with Example 1, Comparative Examples 4, 5, and 6 respectively use sodium ethanesulfonate iminoglutaric acid, stearic acid, and sodium ethanesulfonate iminoglutaric acid to modify the zinc powder. The agglomeration problem and dispersibility of the zinc powder are improved to a certain extent, and the storage stability of the coating is improved. However, the compatibility between sodium ethanesulfonate iminoglutaric acid, stearic acid, and sodium ethanesulfonate iminoglutaric acid and the epoxy resin emulsion is poor, and there is no good compatibility between the modified zinc powder and the epoxy resin emulsion. After long-term storage, sediment is generated, the storage stability is poor, and the impact resistance, corrosion resistance, and salt spray resistance of the paint film are lower than those of Example 1.
[0066] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A water-based epoxy zinc-rich coating for containers, characterized in that: The water-based epoxy zinc-rich coating for containers is composed of component A and component B, wherein component A includes 12-18 parts by weight of epoxy resin emulsion, 0.1-0.14 parts by weight of anti-flash rust agent, and 0.1-0.15 parts by weight of defoamer; component B includes 70-80 parts by weight of modified highly dispersible zinc powder, 0.1-1 parts by weight of modified graphene, 2.6-3.2 parts by weight of polyamide curing agent, 10-15 parts by weight of propylene glycol methyl ether, 0.5-0.8 parts by weight of wetting agent, and 1.6-2.5 parts by weight of anti-settling agent; The preparation method of the highly dispersible zinc powder comprises: (1) Add epoxy resin having the structural formula: Sodium ethanesulfonate iminoglutaric acid, after the reaction, cooling, adding acetone, filtering, washing with acetone, and drying to obtain an epoxy resin modifier; (2) Add zinc powder and epoxy resin modifier to water, perform ball milling in a high-speed ball mill, filter, and dry to obtain highly dispersible zinc powder.
2. The water-based epoxy zinc-rich coating for containers according to claim 1, characterized in that: The reaction in (1) is carried out at 80-90°C for 3-5h.
3. The water-based epoxy zinc-rich coating for containers according to claim 1, characterized in that: The mass ratio of epoxy resin to sodium ethanesulfonate iminoglutaric acid in (1) is 100:(76-82).
4. The water-based epoxy zinc-rich coating for containers according to claim 1, characterized in that: The mass ratio of zinc powder to epoxy resin modifier in (2) is 100:(1-3); and the ball milling time is 1-2h.
5. The water-based epoxy zinc-rich coating for containers according to claim 1, characterized in that: The preparation method of the modified graphene comprises: adding graphene oxide to thionyl chloride for reaction to obtain chlorinated graphene; then adding the chlorinated graphene to dichloromethane, adding triethylamine and sodium ethanesulfonate iminoglutaric acid after ultrasonic dispersion, reacting for 18-24 hours, filtering, washing with water, and drying to obtain the modified graphene.
6. The water-based epoxy zinc-rich coating for containers according to claim 5, characterized in that: The mass ratio of the graphene chloride, triethylamine and sodium ethanesulfonate iminoglutaric acid is 100:(120-500):(300-1200).
7. The water-based epoxy zinc-rich coating for containers according to claim 1, characterized in that: The preparation method of sodium ethanesulfonate iminoglutaric acid comprises: adding glutamic acid and sodium carbonate to water, adding sodium 2-bromoethanesulfonate after stirring, heating to 75-80° C. for reaction for 2-3 hours, adding saturated sodium chloride solution after cooling, extracting with ethyl acetate, concentrating the organic phase under reduced pressure, adding the product to water, heating to evaporate and concentrate, cooling in an ice water bath for crystallization, and drying to obtain sodium ethanesulfonate iminoglutaric acid.
8. The water-based epoxy zinc-rich coating for containers according to claim 7, characterized in that: The molar ratio of the glutamic acid, sodium hydroxide and sodium 2-bromoethane sulfonate is 1:(1-1.1):(1-1.1).
9. A method for preparing a container waterborne epoxy zinc-rich coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises: adding an anti-flash rust agent and a defoaming agent to an epoxy resin emulsion, stirring and dispersing, and obtaining a component A; Add modified highly dispersible zinc powder, modified graphene, polyamide curing agent, wetting agent and anti-settling agent to propylene glycol methyl ether, stir and disperse to obtain component B; add component B to component A, stir and mix to obtain water-based epoxy zinc-rich coating for containers.
Citation Information
Patent Citations
Waterborne epoxy zinc-rich coatings containing microcapsule-modified zinc powder and their preparation
CN105385305B
Epoxy grafted graphene finish paint for new energy automobile and preparation method of epoxy grafted graphene finish paint
CN106634418A
Graphene modified water-based epoxy zinc-rich coating and preparation method and application thereof
CN108795235A
Conductive graphene composite coating for automobile and preparation method of coating
CN112375461A
Composite nano cold galvanizing coating and preparation method thereof
CN117925070A